How Dedication to The Inspectorate of Central Kalimantan Province Affects The Competence And Ethics Of Internal Government Supervisory Apparatus? - Marfengki Wanto; Meitiana Meitiana; Luluk Tri Harinie (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research was conducted to analyze the influence of competence, commitment, and ethics variables on responsibility at the Inspectorate of Central Kalimantan Province. This research was designed to quantitatively use explanatory research methods with a causality approach design or a causal relationship between two variables. Following the research location at the Inspectorate of Central Kalimantan Province, the total population of employees serving as APIP is the Government Oversight Function (PPUPD) and Auditor Functional, who are directly involved in supervisory activities. The samples used in this study were all APIPs in the Inspectorate of Central Kalimantan Province, namely 64 people. The research instrument used in this study was a structured questionnaire equipped with alternative answers. The respondent only had to choose the alternative that best suited the respondent's experience, opinion, or feelings. Data analysis uses the help of SPSS and Smart PLS statistical analysis tools. The findings from this study are that the competence variable has a significant direct effect on commitment. The ethical variable has no significant impact on loyalty. Competence, ethics, and commitment have no significant effect on performance. Meanwhile, from the results of the indirect effect test, the commitment variable cannot mediate the influence of competence on performance. It is also unable to mediate the effect of ethics on performance.